INTEGRITI DALAM KALANGAN PELAJAR MUSLIM DI IPTA: SATU TINJAUAN AWAL: INTEGRITY AMONG MUSLIM STUDENTS IN PUBLIC UNIVERSITIES: A PRELIMINARY REVIEW - Eusope, Noraeyn; binti Abdul Ghani Azmi , Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2021)
The purpose of this preliminary review is to evaluate the effectiveness of the research instrument in identifying the level of academic and social integrity among the Muslim IPTA students in Malaysia. The quantitative study was conducted by using digital questionnaires. The study instruments were adapted from the studies of Anis Yusal (2017), Arieff Salleh Rosman et al, (2008), Nur Hafizah Yusoff (2019), Norhasilah Mat Nor (2012) and Nor Wahida (2018). Data were collected from 30 university students from various disciplines. The analysis was done by using software of IBM Statistical Package of Social Science (SPSS) version 26. The value for the Alpha Cronbach is 0.756. The analysis of data on demographic of the respondents and integrity were done using the descriptive and frequency test. For integrity, the study showed that majority of the students understand the concept of integrity. However, most of them had committed some academic integrity misconduct. As for social integrity, some agreed to several social values which are against the noble values in integrity. This contrasting finding is a concern and need to be addressed accordingly by virtue of deeper understanding on Islam as a way of life and becoming a highly integrity person. In the perspective of Islam, integrity is the value in oneself which is in line with the nature of trust, honesty, faith, strong belief, strict adherence to Islamic rules and noble manners.